Učinkovitost logopedske telerehabilitacije otrok - Slana, Nuša (Rehabilitacija (Ljubljana), 2021)
Objective: The COVID-19 epidemic has greatly affected the delivery of all health services, including speech and language therapy. Foreign authors established that the use of telerehabilitation in speech and language pathology has increased significantly. Recently, the need for telerehabilitation has also appeared at our Department for the habilitation and rehabilitation of children. Our aim was to review the available literature about the effectiveness of telerehabilitation in pediatric speech and language pathology. Methods: The Eric, PubMed and Apa PsycInfo databases were searched, using key words: speech and language pathology, children, paediatric, telerehabilitation, telepractice and internet. A systematic review was conducted in accordance with PRISMA guidelines. Results: We included 11 papers that fulfilled the inclusion criteria. The results of the included studies support the use of telerehabilitation in the process of speech and language assessment and intervention. All children included in the telerehabilitation showed progress. The service delivery method did not statistically significantly affect the effectiveness of therapy. Conclusion: The use of speech and language telerehabilitation has proved to be an effective and feasible method of assessing speech and language development as well as delivering the treatment of speech and language disorders. There is a need for further research on the use of telerehabilitation in children with neurological disorders.
Keywords: child; effectiveness; feeding and swallowing disorders; govorno-jezikovne motnje; logopedija; motnje hranjenja; otrok; rehabilitation; speech and language disorders; Speech Disorders; speech-language pathology; telerehabilitacija; Telerehabilitation; učinkovitost